Integrated operations in the oil and gas industry sustainability and capability development - Rosendahl, Tom; Hepsø, Vidar (Business Science Reference, 2013)
"This book covers the capability approach to integrated operations in the oil industry, referring to the combined capacity and ability to plan and execute in accordance with business objectives through a designed combination of human skills, work processes, organizational change, and technology"--Provided by publisher.
Keywords: Petroleum industry and trade -- Management.; Petroleum industry and trade -- Information technology.; Gas industry -- Management.; Gas industry -- Information technology.; elektronické knihy; electronic books